EFEKTIVITAS TEKNOLOGI APLIKASI PT. GO-JEK INDONESIA DI SOLORAYA - Dian Esti Nurati, Siswanta, Pungky Larasati, (Solidaritas, 2018)
ABSTRACTPT. GO-JEK INDONESIA is one of business entity that concentrate in business field in transportation service industry sector which focuses on Ojek online (GO-JEK) . The company was founded by Nadiem Makarim in 2011 and Go-Jek is present at Solo city on May 26th, 2016. Go-Jek presents a communications technology based on mobile internet applications, where this application is effectively used in everyday activities. This study aims to describe the effectiveness of PT application technology. Go-Jek Indonesia in Soloraya. The theory used in this research is communication technology of mobile internet application and communication effectiveness. The research methodology used is descriptive qualitative research. Sources of data used are primary and secondary data. Data collection techniques in this study use interview techniques, observation and documents. Validity of data is using data triangulation technique. Data analysis techniques performed with data reduction, data presentation and conclusions. In conclusion that application technology PT. Go-Jek Indonesia has given effectiveness and changes the consumer action patterns in the use of Go-Jek applications in everyday life. This effectiveness is seen from the effects of consumers who prefer Go-Jek than conventional services or other online transportation services.Keywords: communication technology, Go-Jek app